On the use of centrality measures to determine connected dominating sets for mobile ad hoc networks. (2017) - Meghanathan, Natarajan
We investigate the use of centrality measures to determine connected dominating sets (CDSs) for mobile ad hoc networks (MANETs) whose topology changes dynamically with time. CDSs are preferred for performing network-wide broadcasts with reduced retransmissions. Though commonly used, degree centrality-based CDS has been observed to be quite unstable in the presence of node mobility. In this paper, we explore the use of other centrality measures (such as eigenvector centrality, betweenness centrality and closeness centrality that are commonly used for complex network analysis) as the underlying criterion for inclusion of nodes in a CDS for MANETs and evaluate the lifetime and node size of such CDSs in comparison to that incurred for the degree centrality-based CDS. We observe the eigenvector centrality-based CDS to be the most stable (but the CDS node size is also the largest); the betweenness centrality-based CDS is the least stable (but incurs the smallest CDS node size).